Atmospheric Stability and Its Effect on The Polluted Columns of Concentrations in North West of Baghdad City - Hassoon, Ahmed; Mohammed, Samar; Al-Saleem, Hazim (Iraqi Journal of Science, 2023)
Atmospheric stability plays the most important role in the transport and dispersion of air pollutants. Different methods are used for stability determination with varying degrees of complexity. Most of these methods are based on the relative magnitude of convective and mechanical turbulence in atmospheric motions, such as Richardson number, Monin-Obukhov length, Pasquill-Gifford stability classification and Pasquill-Turner stability classification. The Pasquill-Turner Method (PTM), which is employed in this study used Observations of wind speed, solar altitude angle and the time of day to classify atmospheric stability with distinguishable indices. As a case study, meteorological data that gathered from European Centre For Medium-Range Weather Forecasts (ECMWF) at latitude 33.750 and longitude 43.870 that Located north west of Baghdad city ( this area consider suburban that a crosses domain wind towards city center) through hours 00,03,06,09,12,15,18,21 from every day in 2010 year . The scheme used two different categories are considered to deduce the pattern of atmospheric stability conditions. First, the annual or total pattern of stability classification is obtained and results show that atmosphere is 54.4 %, 8.7 %, 36.9 %, at stable, neutral and unstable conditions, respectively. It is also observed that days are mostly unstable (61.6%) while nights are mostly stable (94.5%). Second, monthly and seasonal patterns are derived and results indicate that relative frequency RF% of stable conditions decrease during January to June and increase during June to December, while results for unstable conditions are exactly in opposite manner. Autumn is the most stable season with relative frequency of 62.1% for stable condition, whilst, it is 56.2 %, 44.6 % and 54.6% for winter, summer and spring, respectively. Finally, correlation between RF% of stable conditions and NOX, SO2, CO, CH4 columns concentrations in(kg/m2) is achieved and results show correlation between these elements and stability .The important of this study basically located in assessment air quality of Baghdad city and also in urban planning.